1980
DOI: 10.1128/jcm.12.3.304-309.1980
|View full text |Cite
|
Sign up to set email alerts
|

Separate O-grouping schemes for serotyping clinical isolates of Proteus vulgaris and Proteus mirabilis

Abstract: Antisera were prepared against type strains of the original scheme of B. Perch (Acta Pathol. Microbiol. Scand. 25:703-714, 1948) and against newly defined types to produce separate schemes for O-grouping Proteus vulgaris and Proteus mirabilis. In assessing the schemes for their effectiveness it was found that 82% of 208 P. vulgaris isolates and 88% of 194 P. mirabilis isolates from two hospitals were typable. Only 3.4% of the P. vulgaris isolates agglutinated in P. mirabilis antisera, and 1.5% of the P. mirabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…These and previous findings [5] showed that, together with the major antigens within LPS which define the group specificity of Proteus strains [3,4], there are numerous minor antigens. They provide a serological cross-reactivity of strains belonging to different serogroups and should be taken into account when creating a detailed serological classification scheme of Proteus bacteria.…”
Section: Serological Studies With Proteus Lpssupporting
confidence: 78%
See 1 more Smart Citation
“…These and previous findings [5] showed that, together with the major antigens within LPS which define the group specificity of Proteus strains [3,4], there are numerous minor antigens. They provide a serological cross-reactivity of strains belonging to different serogroups and should be taken into account when creating a detailed serological classification scheme of Proteus bacteria.…”
Section: Serological Studies With Proteus Lpssupporting
confidence: 78%
“…The serological O-specificity of bacterial smooth forms is defined by the structure of the polysaccharide chain of LPS (O-antigen). Based on the O-specificity, two species, P. mirabilis and P. vulgaris, have been classified into 60 O-serogroups [3,4], and a number of additional serogroups have been proposed for the third medically important species, P. penneri [5]. Structures of the O-specific polysaccharides of most Proteus serogroups have been determined and correlated to the immunospecificity of the O-antigens [5].…”
mentioning
confidence: 99%
“…Outer membrane lipopolysaccharide (LPS, endotoxin) is considered as a virulence factor of Proteus. Based on the Ospecific polysaccharide chains of LPS (O-antigens), two species, Proteus mirabilis and Proteus vulgaris, were classified into 60 O-serogroups [1,2], and recently two more O-serogroups, O61 and O62, have been proposed for strains of the third species, Proteus penneri [3,4]. Chemical and immunochemical studies of Proteus LPS are important for understanding the molecular basis of the immunospecificity of Proteus strains and for their classification based on structural and serological data.A peculiar feature of the Proteus LPS is that in most Oserogroups the O-antigens are acidic due to the presence of phosphate groups, hexuronic acids, their amides with amino acids, sugar acetals with pyruvic acid or ethers with lactic acid ([3Ϫ9] and references cited therein).…”
mentioning
confidence: 99%
“…According to the serological classification based on the specificity of the cultures as described [10]. Crude lipopolysaccharide preparations, obtained after extraction of bacterial mass with a hot phe-outer-membrane lipopolysaccharide (LPS, O-antigen), Proteus mirabilis and Proteus vulgaris strains are divided into 60 O-nol/water mixture [11], were purified by treatment with cold serogroups [1,2]. aqueous 50% CCl 3CO2H followed by dialysis of the superna-Recently the name Proteus penneri has been proposed for tant.…”
mentioning
confidence: 99%